2021
DOI: 10.3390/vaccines9020073
|View full text |Cite
|
Sign up to set email alerts
|

Newcastle Disease Virus-Like Particles Displaying Prefusion-Stabilized SARS-CoV-2 Spikes Elicit Potent Neutralizing Responses

Abstract: The COVID-19 pandemic highlights an urgent need for vaccines that confer protection from SARS-CoV-2 infection. One approach to an effective COVID-19 vaccine may be through the display of SARS-CoV-2 spikes on the surface of virus-like particles, in a manner structurally mimicking spikes on a native virus. Here we report the development of Newcastle disease virus-like particles (NDVLPs) displaying the prefusion-stabilized SARS-CoV-2 spike ectodomain (S2P). Immunoassays with SARS-CoV-2-neutralizing antibodies rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(43 citation statements)
references
References 60 publications
(89 reference statements)
2
41
0
Order By: Relevance
“…A soluble trimeric RBD, as applied in BNT162b1 mRNA clinical trials, showed very promising immunogenicity including stimulation of antibodies and T cell responses [81,82]. In addition to trimerization, membrane anchoring seems to further improve immunogenicity, as transmembrane anchored prefusion-stabilized full-length S protein was reported to elicit higher VNA levels than corresponding secreted constructs [1,83]. Both in terms of immunogenicity and potential association of circulating SARS-Cov-2 S1 subunit with enhanced blood clotting [84], use of a small membrane-anchored antigen is rational.…”
Section: Plos Pathogensmentioning
confidence: 99%
“…A soluble trimeric RBD, as applied in BNT162b1 mRNA clinical trials, showed very promising immunogenicity including stimulation of antibodies and T cell responses [81,82]. In addition to trimerization, membrane anchoring seems to further improve immunogenicity, as transmembrane anchored prefusion-stabilized full-length S protein was reported to elicit higher VNA levels than corresponding secreted constructs [1,83]. Both in terms of immunogenicity and potential association of circulating SARS-Cov-2 S1 subunit with enhanced blood clotting [84], use of a small membrane-anchored antigen is rational.…”
Section: Plos Pathogensmentioning
confidence: 99%
“…This has been evaluated in several preclinical and clinical trials, and recently, a vaccine against the circumsporozoite protein of the malaria pathogen has been locally approved (European Medicines Agency, 2015). Recent efforts to develop VLP‐based severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) vaccines underline the flexibility and simplicity of chimeric VLPs (Ghorbani et al, 2020; Yang et al, 2021). However, the versatile platform of chimeric VLPs not only comes with promises, but also with fundamental challenges, such as the ability to form stable capsids (Borisova et al, 1999; Böttcher et al, 2006; Nassal et al, 2005; Pumpens & Grens, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…A candidate poised for rapid advancement is avian pathogen Newcastle disease virus-like particles (NDVLPs) used to display pre-fusion stabilized SARS-CoV-2 S ectodomain (S2P) [39]. The S2P transmembrane and cytoplasmic domains were replaced with those from NDV to create a fusion protein that when co-expressed with NDV matrix and nucleocapsid proteins form S2P-NDVLPs.…”
Section: Antigen-presenting Nanoparticles 221 Virus-like Particlesmentioning
confidence: 99%